Santos, Boaventura de Sousa (2015). La universidad en el siglo XXI. México: Siglo XXI, 173 páginas - Bernal Aguirre, Juan (2016)
Reseña Santos, Boaventura de Sousa (2015). La universidad en el siglo XXI. México: Siglo XXI, 173 páginas